2011
DOI: 10.1111/j.1528-1167.2011.03168.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk and prognostic factors of status epilepticus in the elderly: A case-control study

Abstract: consecutive patients aged 70 years or older with SE were included. Each patient was matched to three controls without SE seen during the same period. Matching variables were age (±3 years), gender, and comorbidity index (±3). Multivariate logistic regression model were used to compare cases to controls and, among the cases, nonsurvivors to survivors. Key Findings: By multivariate analysis, factors independently associated with SE were acute decompensation (cardiac, respiratory, or hepatic) [adjusted odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
2
31
0
3
Order By: Relevance
“…In the Asian continent, a not-so-different demographic profile is found, with a fairly equal sex distribution with 53%–57% males, a male-to-female ratio of 1.35:1 and an incidence of the first SE episode of 42/100,000/year [14,15,16]. Meanwhile, countries like Italy, France and Switzerland have an inverse male-to-female ratio [17,18,19,20]. According to the study by Chin et al, the incidence of SE in children 15 or younger in the U.K. is 14.5/100,000/year, being the highest for those aged one year or less with an incidence of 51/100,000/year [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Asian continent, a not-so-different demographic profile is found, with a fairly equal sex distribution with 53%–57% males, a male-to-female ratio of 1.35:1 and an incidence of the first SE episode of 42/100,000/year [14,15,16]. Meanwhile, countries like Italy, France and Switzerland have an inverse male-to-female ratio [17,18,19,20]. According to the study by Chin et al, the incidence of SE in children 15 or younger in the U.K. is 14.5/100,000/year, being the highest for those aged one year or less with an incidence of 51/100,000/year [21].…”
Section: Resultsmentioning
confidence: 99%
“…7.9 95% C.I. 3.3–19.15), along with trauma, acute cardiac, respiratory or hepatic decompensation, epilepsy and dysnatremia were factors significantly associated with SE [19]. In a recent study of a large administrative database, Urtecho et al found that risk factors for SE in patients with severe sepsis and septic shock were younger age, female gender, black race, the presence of metabolic derangements and renal and respiratory dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 The cohort of the present analysis has its own specificity, as it includes mostly refractory, non-convulsive SE without coma in elderly patients, a population being at higher risk of intensive care complications, 22,23 and therefore less often managed in intensive care units. 20,21 The cohort of the present analysis has its own specificity, as it includes mostly refractory, non-convulsive SE without coma in elderly patients, a population being at higher risk of intensive care complications, 22,23 and therefore less often managed in intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is reminiscent of the setting of post-anoxic coma, where patients managed with continuous EEG do not have better prognosis as compared to those receiving only routine recordings. 20,21 The cohort of the present analysis has its own specificity, as it includes mostly refractory, non-convulsive SE without coma in elderly patients, a population being at higher risk of intensive care complications, 22,23 and therefore less often managed in intensive care units. The two groups had the same characteristics in terms of SE severity (STESS score) and proportion of underlying severe causes.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference could be proven for the subgroups, refractory NCSE or refractory CSE, however, de novo seizures were associated with a trend towards a poorer prognosis. Previous studies have shown this correlation for SE in general, whereas the findings for refractory SE have been inconsistent (Drislane et al ., ; Novy et al ., ; Canoui‐Poitrine et al ., ; Hocker et al ., ). A possible explanation is that refractoriness by itself is a marker of a severe event, and that the damage caused by the SE overshadows the prognostic value of a de novo situation.…”
Section: Discussionmentioning
confidence: 98%